Urgensi Pendidikan Bagi Kepemimpinan - Hamdi Abdillah (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
This study focuses on discussing Islamic education and its urgency for leadership in Muslim society, through exploring the meaning of education, leadership and human nature in depth and comprehensively, then revealing the urgency of education for leadership in Muslim society. This research uses library research method with qualitative content analysis technique. This study resulted in three conclusions; 1) Humans have a nature that is able to organize and control themselves and even the universe, because that nature is a divine potential that is only given by God to humans; 2) Education in Islam is not limited to formal, non-formal and informal education, Islamic education is wider than that, as evidenced by QS al-Alaq: 1-5 which was chosen as the first revelation to the Prophet. In addition to hinting at Islam's main concern for education, the verse also implies that knowledge is not limited; 3) leadership in Islam is something that cannot be separated from humans. At least humans become leaders for themselves. Leadership is ingrained in him and needs to be developed by unlimited education.